Tribological behavior of a contact pin on cylinder CuSn7 bronze rubbing against 20MnCr5 steel in dry sliding with electrical current / Bekhouche Djamel...[et al.] - Bekhouche, Djamel; Bouchoucha, Ali; Hamid, Zaidi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The tribological behavior of CuSn7 Bronze and Steel 20MnCr5 couple was studied as a function of mechanical and electrical parameters and the contact geometry (pin on cylinder) under ambient environment. To do this, a pin on cylinder tribometer (the test machine is a kind of pin-on-slip ring) was used. Experimental results show that these parameters have a significant effect on the friction and on the wear. Indeed, the load has a significant influence on the tribological behavior of the couple both with and without electrical current. In the other hand, the friction coefficient and wear of the pin against the cylinder decreases especially at high values of electrical current. Moreover, the observed wear mechanisms are: adhesion, abrasion, oxidation, arc erosion and plastic deformation. At high applied electrical current and loads, the main wear mechanism is the arc erosion and severe plastic deformation. The discussion of the obtained results is based on examination of the worn surfaces and analysis performed on interfacial phenomena observed during the friction process.